The Correlation of Positive Reinforcement, Self-Confidence, and Speaking Performance of English Young Learners - Samodra, Opini Ala; Faridi, Abdurrachman (English Education Journal, 2021)
Most teachers may face challenges to teach the students without students’ native language to teach a foreign language. The students may get bored easily and not motivated because they have to listen to more new strange words in every meeting that they do not directly understand the words means. Thus, it needs some strategies to get the better result. Students who like doing things happily need a more relaxing learning situation to join the English classes comfortably. The study aimed to investigate the correlation of verbal, gestural, token reinforcement, speaking performance, and self-confidence. The research method used was a quantitative study with multiple linear regressions. Students of the fifth grade of SD N 1 Wates Undaan Kudus as the population took part in the positive reinforcement, self-confidence, and speaking performance test in teaching English. The data were analyzed through a statistical program of SPSS 22. Thus, there was a correlation between positive reinforcement, speaking performance, and self-confidence. The conclusion is that all positive reinforcement correlates with speaking performance and self-confidence. It means that the positive reinforcement influenced their speaking performance and their self-confidence. It is suggested that the teacher should raise their awareness to motivate students’ speaking skills for better achievement. Besides, teachers’ performance in the classroom activity deals with classroom management, encourages the students to always joyful in learning English materials, provides exercise and group discussion according to their circumstance, and performs various teaching that involves the learner’s role in the classroom activity.